2010
DOI: 10.1021/cb100266g
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Neurotransmitters as Substrates for Novel Tick Sulfotransferases, Homology Modeling, Molecular Docking, and Enzyme Kinetics

Abstract: Blacklegged ticks (Ixodes scapularis) transmit the causative agent of Lyme disease in the Northeastern and upper Midwestern US. Current research focuses on elucidating biochemical pathways which may be disrupted to prevent pathogen transmission, thereby preventing disease. A genome screening process reported transcripts coding for two putative sulfotransferases in salivary glands of adult Ixodes scapularis and in whole tick extracts of the nymphal and larval stages. Sulfotransferases are known to sulfonate phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…One provocative possibility is that one or more of Hk1's PBPs bind neurotransmitters, which are derived from amino acids and would be released by the host in response to tissue injury (i.e., formation of the feeding lesion) (Askenase et al, 1995; Dai et al, 2010; Theoharides et al, 2012). Tick saliva also contains a plethora of bioactive molecules, including dopamine and dopamine sulfate (Koci et al, 2014; Simo et al, 2012; Simo et al, 2011; Yalcin et al, 2010). Interestingly, using qRT-PCR, we recently reported significantly greater induction of c-di-GMP-dependent genes by B. burgdorferi in feeding nymphs compared to larvae (Caimano et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One provocative possibility is that one or more of Hk1's PBPs bind neurotransmitters, which are derived from amino acids and would be released by the host in response to tissue injury (i.e., formation of the feeding lesion) (Askenase et al, 1995; Dai et al, 2010; Theoharides et al, 2012). Tick saliva also contains a plethora of bioactive molecules, including dopamine and dopamine sulfate (Koci et al, 2014; Simo et al, 2012; Simo et al, 2011; Yalcin et al, 2010). Interestingly, using qRT-PCR, we recently reported significantly greater induction of c-di-GMP-dependent genes by B. burgdorferi in feeding nymphs compared to larvae (Caimano et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Except for the sections “P0 Sequence Identification,” “Sequence Alignments” and “TtP0 Motif Analysis,” the procedures described below are based on the methods of Yalcin et al …”
Section: Methodsmentioning
confidence: 99%
“…This, in itself, can reduce dopamine function leading to many RDS behaviors, including depression and possibly, anxiety. In fact, it was shown that activity of Ixosc Sult 1 and Sult 2 in the Ixodid tick salivary glands might contain inactivation of the salivation signal through sulfonation of either dopamine or octopamine [32]. …”
Section: The Dopamine Connectionmentioning
confidence: 99%